If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 + -4y = 32 Solving -24 + -4y = 32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -4y = 32 + 24 Combine like terms: -24 + 24 = 0 0 + -4y = 32 + 24 -4y = 32 + 24 Combine like terms: 32 + 24 = 56 -4y = 56 Divide each side by '-4'. y = -14 Simplifying y = -14
| 16+4x=2x+8 | | 2n+6n-14=-2(-4n+12) | | 12m-16=-64 | | 7-3m=16 | | w/3=-10 | | 9-12m=-21 | | 5u^2-2u-72=0 | | y=6*-3+4 | | 2x+5x-4=4 | | 5x^6-2x^3-72=0 | | 2e+4e-3e= | | -4+7y=3 | | (z/7)=5=4 | | 0.04-0.02=0.5 | | 2+6=33 | | 9q+6q=63-3 | | 7+9=127 | | 2x^3-7x-6=0 | | 7+9=172 | | y=4*-1-2 | | n=1.05/.7 | | $59.99-20%= | | 4h-3h+4=5 | | 11+4=152 | | 7+5lnx=45 | | -25-2y=-3 | | (3x-2)(x+1)=0 | | (8x+3)+(-9x+9)= | | 21n+3=7n-3 | | 3-6n=12+3 | | ln(x)=0.0875 | | log(x)=0.085 |